SAT0353 Relationship between Disruption of The Muscular Layer in Temporal Artery Biopsies of GCA Patients and The Development of Aortic Dilatation/aneurysm during Follow-Up. (15th July 2016) - Murgia, G.; Hernández-Rodríguez, J.; García-Martínez, A.; Prieto-González, S.; Alba, M.A.; Espigol-Frigole, G.; Villar, I.; Campo, E.; Sánchez, M.; Arguis, P.; Grau, J.M.; Cid, M.C.
Abstract : Background: Giant cell arteritis (GCA) may be complicated by aortic dilatation/aneurysm (aortic structural damage; ASD), which may lead to life-threatening events. In GCA patients, ASD occurs 17.3 times more frequently than in the general population, affecting up to 33.3% of patients after long term follow-up 1 . ASD is in most cases a delayed complication and its pathophysiology is unclear. Necropsy/surgery specimens from patients subjected to standard treatment and control may reveal persistent inflammatory infiltrates but these are usually mild or absent and extensive disruption of elastic fibers is the most striking finding 2 . We hypothesized that extensive loss of vascular smooth muscle cells during the initial injury may prevent regeneration of elastic fibers and contribute to aortic wall weakening and subsequent dilatation. Objectives: To assess whether the extent of medial layer injury in temporal artery biopsies (TABs) predicts subsequent development of aortic dilatation. Methods: We performed histopathological scoring of TABs from all biopsy-proven GCA patients that underwent thoracic CT examination during follow-up for any reason. Aortic diameters in the ascending aorta, aortic arch and descending aorta were measured and ASD was defined as described 1, 2 . Histopahotlogical scoring was performed as reported 3 . Fisher exact test and Kaplan-Meier estimates and long-rank test were used for statistical analysis. Results: Between 1995 and 2013, 144 patients with biopsy-proven GCA were subjected to a chest CT. In 36 (25%) patients, this was part of a prospective screening protocol for large-vessel involvement in newly diagnosed patients 4, in 94 (65.3%) CT was part of a prospective detection of a ASD 2, and in 14 (9.7%) CT was performed for a variety of medical indications. ASD was detected in 34 (23.6%) patients after a median follow up of 55.5 months (range 0–156). In 43 (29.9%) of biopsies inflammatory infiltrates preserved the medial layer and in 101 (70.1%) inflammation was panarteritic severily disrupting the structure of the media which could be hardly identified. ASD was detected at some point in 28 (27.7%) of patients with panarteritic involvement and in 6 (14%) of patients with a preserved media. However, differences did not reach statistical significance (p=0.089). In patients with panarteritic involvement, ASD was detected after a mean follow-up of 53.9 months (SD±37.7) whereas in patients with a preserved media ASD was observed after a mean follow-up of 74.1 months (SD±35.2) (p=0.094). Conclusions: Patients with severe disruption of the medial layer in their temporal arteries at diagnosis had a trend to develop more frequent and earlier ASD, although differences did not reach statistical significance. Further studies are necessary to clarify this point. Supported by Maratό TV3 2014/201507 References: García-Martínez A et al Ann Rheum Dis 2014 García-Martínez A et al Arthritis Rheum 2008 Hernández-Rodriguez J et al Medicine 2016 Prieto-González S et al Ann Rheum Dis 2012 Disclosure of Interest: None declared